Image-Guided Percutaneous Aspiration and Gelfoam Treatment of Petrous Apex Cholesterol Granuloma: A New Theory and Method for Diagnosis and Treatment - Lee, Thomas C.; Raghavan, Deepak; Curtin, Hugh D. (Journal of Neurological Surgery Part B: Skull Base, 2013)
Although diagnosis of cholesterol granulomas of the skull base can be straightforward with computed tomography (CT) and magnetic resonance imaging (MRI) appearance, treatment is controversial with various skull base approaches described in the literature. This report describes a 35-year-old man who presented with a symptomatic, enlarging cystic lesion in the left petrous apex and clivus that had imaging features of a cholesterol granuloma (cholesterol cyst). Due to a prior history of treated mediastinal germ cell tumor, pathologic confirmation of the lesion was requested. A CT-guided percutaneous aspiration revealed dark used motor oil–like fluid. Continued aspiration yielded a change in the character of the fluid to marrow red. Injection of contrast revealed no communication with cerebrospinal fluid. Gelfoam (Pfizer, New York, New York, USA) was subsequently injected percutaneously into the residual cavity. Histopathology showed no evidence of malignancy and follow-up MRI at 1 month, 3 months, 6 months, and 1 year demonstrated continued decrease in size and signal of the lesion.
Keywords: cholesterol granuloma; petrous apex; Gelfoam; image guided